Real-time testing of the failure process and rupture time prediction in thermal barrier coatings using accoustic emission. - Lu, Chungsheng; Yang, L.; Zhou, Y. (CSTAM and Herbin Institute of Technology, 2011)
The real-time testing and quantitative assessment of damage evolution in thermal barrier coatings (TBCs) is desirable, but still intractable. In this paper, the fracture process of TBCs subjected to mechanical or thermal loading are monitored using an acoustic emission method. Based on the wavelet analysis of acoustic emission signals, damage modes in TBCs are discriminated. The results show that, due to thermal stress, it is preferential for vertical cracks in the heating stage and interface cracks in the cooling stage, and the failure of thermal barrier coatings originates from surface vertical cracking and follows interface cracking under tensile loading. The surface crack density and interface crack length are calculated to obtain the quantitative correlation of damage evolution in TBCs and acoustic emission parameters. The cracking source identified from AE signals agrees well with that observed by optical microscopy. The rupture time of TBCs can be predicted by the statistical analysis of acoustic emission signals.